2016
DOI: 10.1097/gme.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between hormone therapy and dry-eye syndrome in postmenopausal women

Abstract: The current study findings have negated the previous assumption that HT use contributes to a reduction in DES among postmenopausal women. Instead, prolonged HT use seems to increase the risk of DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…[14] It has also been reported that greater doses of both estrogen only and estrogen plus progesterone HRT result in increased dry eye symptom severity compared with lower doses of the same treatments. [8] Other studies have found that HRT actually decreases ocular complaints and increases the quantitative tear production. [1516] Further, Jensen et al .…”
Section: Effects Of Hormonal Replacement Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…[14] It has also been reported that greater doses of both estrogen only and estrogen plus progesterone HRT result in increased dry eye symptom severity compared with lower doses of the same treatments. [8] Other studies have found that HRT actually decreases ocular complaints and increases the quantitative tear production. [1516] Further, Jensen et al .…”
Section: Effects Of Hormonal Replacement Therapymentioning
confidence: 99%
“…The effects of estrogen plus progesterone therapy are less clear, but the most recent and largest controlled study showed a dose-dependent increased risk of dry eye symptoms in women taking estrogen and estrogen plus progesterone HRT. [8] The authors of this study suggest that the reason for the discrepancy in results is that the studies finding beneficial effects of HRT were more prone to selection bias and subjectivity as they relied on patient's reports of symptoms and numerous caregivers were used. [8]…”
Section: Effects Of Hormonal Replacement Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…75 Higher doses and increased duration of treatment were also associated with increased DED risk. 90 Oral contraceptive use in premenopausal women was also associated with increased severity of DED based on patient questionnaires. 91 The loss of estrogen receptors in postmenopausal women may explain why hormone replacement therapy is ineffective in this population.…”
Section: Dry Eye In Womenmentioning
confidence: 99%